Theories and empirical approaches towards political economy of trade policy - Mohimi, Afsaneh (Kansas State University, 2013)
It is usually preached by economists that trade should be free, but in reality, it is almost always chained. The reason for this discrepancy lies in the fact that trade policies are set in political contexts in which policy makers have different objective function than maximizing economic efficiency. So, endogenous protection literature evolved around the ideas and reasons to explain trade policy as determined under specific political contexts. The early empirical work until late 1980s examined the correlation between different political factors and trade policies. These works were helpful in identifying relative importance of political economy variables, but were criticized to have specifications which were loosely linked with the theories behind them. In recent years with development of theoretical platforms, study of political economy of trade policy has moved to a more structured direction and empirical investigations have been done to link real world data with the model predictions. In this regard, Median Voter model and Grossman-Helpman (GH) model are the main branches of literature. Median Voter model predicts positive tariffs in capital-abundant countries and negative tariffs in labor-abundant ones, but in real world, negative tariffs are rare. Empirical investigation of this model tries to reconcile observed trade policies with median voter model and two of these studies are included in this report. Interest group model is the framework of Grossman-Helpman model in which the effect of organized lobbies in trade policy determination is taken into account. Two empirical studies of this model showed that real world data support this model. By employing modifications in GH model, researchers try to account for factors like lobbying competition and foreign lobbying in explaining data. These results show that foreign lobbying is not necessarily against trade and ignoring lobbying competition may lead to wrong conclusions about welfare mindedness of government.
Keywords: Trade policy; Political economy; Tariff; Economics (0501)